Combined Staged Surgery and Negative-Pressure Wound Therapy for Closure of a Giant Omphalocele - Vlad Laurentiu David; Mihai Cristian Neagu; Aurelia Sosoi; Maria Corina Stanciulescu; Florin George Horhat; Ramona Florina Stroescu; Calin Marius Popoiu; Eugen Sorin Boia (Case Reports in Pediatrics)
The management of giant omphaloceles had always been a point of interest for the pediatric surgeons. Many surgical techniques were proposed, but none of them succeeded to become the standard procedure in closing the congenital abdominal defect. We present a case of giant omphalocele in which we used staged surgical closure combined with a prosthetic patch, with negative-pressure therapy and, finally, definitive surgical closure. Even though a major complication occurred during the treatment, we were able to close the defect without any prosthetic material left in place.